Application of Used Cooking Oil Based Emulsion Liquid Membrane for Rhodamine B Extraction - Hidayati, Nur; Kamaratih, Azzahra Ardya; Purnama, Herry (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Used cooking oil is utilized as a nontoxic and environmentally friendly organic diluent without the need for complicated pretreatment. Cationic dye rhodamine B was chosen as a sample because of its ability to decolorize water and its use as a base material in toxic, carcinogenic, and mutagenic textile dyes. This study investigates the extraction of rhodamine B from water using cooking oil-based Emulsion Liquid membrane (ELM) methods. This approach addresses issues associated with petroleum-based organic diluents commonly used in ELM processes. The research aimed to evaluate the effect of rhodamine B concentrations ranging from 5 to 20 ppm and D2EHPA concentrations from 0.5 to 2.5% on extraction efficiency. The emulsion was prepared using used cooking oil as the diluent, Span 80 as the surfactant, D2EHPA as the carrier, and HCl as the internal phase. The concentration of rhodamine B in the external phase was determined using a UV-Vis Spectrophotometer. Both rhodamine B concentration and D2EHPA concentration significantly affected extraction efficiency. The highest extraction efficiency of 92.83% was achieved with a rhodamine B concentration of 15 mg/L and a D2EHPA concentration of 2.5% (v/v).